Punitive damages or punitive moral damage? "Punitive" compensation as a means to strengthen the protection of the victim's fundamental rights in Peru - Peralta Tripul, Gabriel (2024)
The main objective was to determine the grounds for applying the punitive criterion in the quantification of moral damages as a means to reinforce the protection of the fundamental rights of the victim in Peru. With this, it is intended to support that, given the impossibility of using punitive damages as they have not been introduced in our system by a law, the quantification of moral damages can be used to award punitive damages as a means to reinforce the protection of the fundamental rights of the victim. In order to carry out the above, a socio-legal research method (aimed at analyzing real cases such as sentences) and a dogmatic-legal method (aimed at analyzing the legal foundations of punitive damages and moral damages) have been used in order to fulfill the proposed objective. Finally, some approximations are presented as a conclusion.